The causal effect of age at migration on youth educational attainment - Dominique Lemmermann; Regina Riphahn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We investigate the causal effect of youths' age at immigration on subsequent educational attainment in the destination country. To identify the causal effect we compare the educational attainment of siblings at age 21, exploiting the fact that they typically migrate at different ages within a given family. We consider several education outcomes conditional on family fixed effects. We take advantage of long running and detailed data from the German Socio-Economic Panel, which entails an oversample of immigrants and provides information on language skills. We find significant effects of age at migration on educational attainment and a critical age of migration around age 6. We find that the educational attainment of female immigrants responds more strongly to a high age at immigration than that of males. We can exclude that the causal effect is determined only by language abilities.
Keywords: I21; J61; C21; 330